Diversity of property regimes of Mediterranean coastal lagoons in S. France; implications for coastal zone management. (15th June 2021) - De Wit, Rutger; Chaubron-Couturier, Pénélope; Galletti, Florence
Abstract: We provide a cartography of the current property regimes of permanent coastal lagoons along the coastlines of the Mediterranean Sea for continental France and Corsica, which include both private and public properties. In France, for the latter, the State Domain Code and the General Code of the property of public persons make a clear difference between Public Domain and private property of the different public entities. Public domain represents property that is imprescriptible and inalienable, i.e. the property rights cannot be changed in the future and neither transferred nor sold to somebody else. In contrast, private properties of public entities can be sold or transferred to thirds. Maritime Public Domain (DPM) was created since 1681. DPM has accommodated Public Domain for the French coastal lagoons following their legal definition as "salty ponds (French étangs salés ) with a direct, natural and permanent connection with the sea". However, private landlords battled juridically with the State for centuries both by attacking the pertinence of this definition and claiming ancestral property rights. As a result, before 1980, more than half of the coastal lagoons comprised private properties, representing about a quarter of the lagoon surface. Twelve of 40 coastal lagoons comprise DPM, mainly the larger lagoons (e.g., Salses-Leucate, many lagoons close to Narbonne, Thau lagoon, Berre lagoon), representing 65% of the total lagoon surface. Since its foundation in 1975, the Conservatoire du Littoral, a public body in charge of coastal nature protection, has bought private coastal lagoons properties in twenty of 40 lagoons, representing 22% of the total lagoon surface. These have been designated as inalienable and imprescriptible "Public Domain of the Conservatoire ", safeguarded for nature conservation purposes. Nowadays, private ownership still persists in 13 lagoons representing 3.3% of total surface. The Coastal lagoons in Roussillon (Etangs du Canet and Salses-Leucate), the Hérault department, in the Camargue and in Corsica currently show variable and sometimes fragmented ownership (in addition to the Conservatoire, DPM, private ownership, municipalities, departments). Fragmented ownership is a clear difficulty for the integrated management of coastal lagoons. With currently, 87% of the coastal lagoons as Public Domain, public law and the environmental code have to evolve to tackle the challenges for the conservation and management of coastal lagoons and their connectivity with the other ecosystems on land and in the sea. Graphical abstract: Image 1 Highlights: Today 87% of the surface of the Mediterranean lagoons in France is public domain. It comprises DPM (65%) and domain of the Conservatoire du littoral (22%). Variability and changes of property regimes reflect a historic process. Still existing fragmented ownership jeopardizes integrated management.